A formação de professores para a educação inclusiva e a contribuição da área de educação inclusiva da Fundação Dorina Nowill para Cegos - Lima, Eliana Cunha (2021)
The scope of this research is to analyze how to spread knowledge related to the teachinglearning process of students with visual impairments and to identify the most relevant aspects related to teacher training in the process of including students with blindness and low vision in the regular classroom, based on the Inclusive Lectures Project (Projeto Palestras Inclusivas), developed by the Inclusive Education area of the Dorina Nowill Foundation for the Blind (DNFB). It is a qualitative research of documentary feature, based on the records filed in the DNFB’s database and the author's narrative, who carried out the summary of written and heard testimonies at the end of each of the 27 training courses offered to 1346 teachers from almost all Brazilian States, remotely, in 2020. The results show the gaps in the initial and continued education of regular classroom teachers about visual impairment, especially in relation to the approach of students with low vision, revealing absence of knowledge of its basic features and of the assistive technologies to be used, hindering the development of pedagogical strategies and, consequently, school inclusion. Another important outcome was finding shortage of professionals specialized in visual impairment, resulting in limited educational offers. It was concluded that the DNFB, with the creation of the Inclusive Education area, started to play an important role in the training scenario in the visual impairment area for regular class teachers and signaled the need for expansion and production of several formats of remote education, as a way to reach its target audience more widely, providing the means to contribute to the continued education of teachers across the country